Early induction of C/EBPβ expression as a potential marker of steroid responsive colitis - Bakri M. Assas (Nature Portfolio, 2019)
Abstract The precise mechanism of hydrocortisone immune regulation in the management of colitis is poorly understood. Whilst not without limitations, its ability to suppress pathology and rapidly improve patient clinical outcome is key. We were interested in identifying early markers of therapeutic responsiveness in order to identify patients’ refractory to therapy. Chronic Th1-driven colitis was induced in AKR/J mice using a parasite infection, Trichuris muris. 35 days post infection, mice were treated with low dose hydrocortisone (2 mg/kg/) i.p. on alternate days. Response to therapy was assessed at a systemic and tissue level day 45 post infection. Histopathology, gene and protein analysis was conducted to determine cytokine and transcriptional profiles. The colonic transcriptional profile in steroid treated mice showed significant upregulation of a small subset of T cell associated genes, in particular C/EBPβ, CD4, IL7R and STAT5a. Despite no change in either transcription or protein production in downstream cytokines IFN γ, TNFα IL-17 and IL-10, hydrocortisone treatment significantly reduced colonic pathology and restored colonic length to naïve levels. As expected, steroid treatment of chronic gut inflammation generated significant immunosuppressive effects characterized by histological improvement. Low dose hydrocortisone induced significant upregulation of a subset of genes associated with T cell maintenance and regulation, including C/EBPβ. These data suggest that enhanced expression of C/EBPβ may be one of a subset of early markers demonstrating an immune regulatory response to hydrocortisone therapy, potentially by stabilization of Treg function. These observations contribute to our understanding of the immune landscape after steroid therapy, providing a potential markers of therapeutic responders and those refractory to hydrocortisone treatment.